2020
DOI: 10.1002/jcc.26413
|View full text |Cite
|
Sign up to set email alerts
|

Influence of back donation effects on the structure of ZnO nanoclusters

Abstract: The structure and properties of ZnO quantum dots is a very popular and rapidly growing field of research for which accurate quantum calculations are challenging to perform. Since the dependence between system size and wall time scales nonlinearly, certain compromises have to be made. A particularly important limiting factor is the size of the basis used, this is especially the case if accurate large calculations are to be carried out. In our work, we discovered that an important O(2p)->Zn(4p) back donation, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…2− using the VASP code is 5.51 eV (see Table 2), which is in excellent agreement with the experimental value of 5.55 eV. 5 Numerous studies of small clusters have been carried out in the past using the VASP code, which have yielded reliable results in agreement with experiments and with those computed using Gaussian. The interpretation of any properties such as the density of states must be independent of the computational code used.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…2− using the VASP code is 5.51 eV (see Table 2), which is in excellent agreement with the experimental value of 5.55 eV. 5 Numerous studies of small clusters have been carried out in the past using the VASP code, which have yielded reliable results in agreement with experiments and with those computed using Gaussian. The interpretation of any properties such as the density of states must be independent of the computational code used.…”
supporting
confidence: 80%
“…The above results as well as the binding energies of Zn in the ZnBeB 22 (CN) 23 and ZnBeB 11 (CN) 12 clusters are found to be nearly the same, namely, 7.04 and 7.09 eV, and 6.33 and 6.37 eV, respectively, for the basis sets 6-311+G(d, p) and 6-311G(d,p). Note that Gutsev et al 5 recently studied the interaction of Zn with O and found that the diffuse functions increase the Zn-O binding energy significantly. The authors argued that this is due to the back donation from Zn 4p to O.…”
mentioning
confidence: 99%
“…The optimization calculations were also carried out at the B3LYP/6-311+G(d,p) level of theory to explore the effect of a higher basis set on energy and spectral properties. 37 Hereafter, unless mentioned, all further calculations refer to B3LYP/6-31G(d,p) optimized geometries. The optimized geometries of both basis sets were subjected to Hessian calculations, which confirmed that the geometries were stationary points on the respective potential energy surfaces.…”
Section: ■ Computational Methodologymentioning
confidence: 99%
“…The model substrate structures, Zn 3 O 3 ( P ); Zn 2 MgO 3 ( S ); and Zn 3 O 3 Mg ( I ), and the complex geometries, (1) CZP : (CO 2 interacting with the Zn site of P ); (2) CZS (CO 2 interacting with Zn site of S ); (3) CMS : (CO 2 interacting with Mg site of S ); (4) CZI : (CO 2 interacting with Zn site of I ); and (5) CMI : (CO 2 interacting with Mg site of I ), were optimized using the B3LYP/6-31G­(d,p) , level of computational model (see Tables S1­(a–h)). The optimization calculations were also carried out at the B3LYP/6-311+G­(d,p) level of theory to explore the effect of a higher basis set on energy and spectral properties . Hereafter, unless mentioned, all further calculations refer to B3LYP/6-31G­(d,p) optimized geometries.…”
Section: Computational Methodologymentioning
confidence: 99%